Keputusan Menjadi Nasabah Bank Muamalat KCP Purwakarta Ditinjau Dari Pengetahuan Calon Nasabah - Fitri Heryani; Ahmad Damiri; Jalaludin (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2020)
The perception of most people about Islamic banks is still very shallow, only limited to knowing that Islamic banks do not use interest but use a profit sharing system. So the bank muamalat kcp purwakarta is required to further increase public knowledge about Islamic banks. The higher knowledge of Islamic banks makes the higher the possibility of adopting Islamic banks. This study aims to see the extent of the influence of customer knowledge (product knowledge (X1), purchasing knowledge (X2), usage knowledge (X3)) on the decision to become a customer of Islamic banks in Purwakarta and to know and analyze how the influence of the three variables when tested together (simultaneous) of the decision to become a customer of Islamic banks in Purwakarta. This research was conducted on Bank Muamalat KCP Purwakarta customers, with a sample of 99 people taken by random sampling. Using descriptive analysis to explain research data and research descriptions, this type of research is a quantitative method. The variables to be examined in this study are the influence of product knowledge (X1), purchasing knowledge (X2), usage knowledge (X3) as the independent variable and the decision to become customers as the dependent variable (Y).Based on the results of the analysis, the research can be summarized as follows: 1). The effect of X1 on Y with a tcount 1.197<ttable 1.985, so it can show that there is no effect of X1 on Y; 2). The effect of X2 on Y with the tcount 0.894 <ttable 1.985, shows that there is no effect of X2 on Y; 3). The influence of X3 on Y with a tcount 4.618> ttable 1.985, shows that there is an influence of X3 on Y; 4). The influence of X1, X2 and X3 on Y with a Fcount 7.451> Ftable 2.70 with a significance value (sig) 0.000 <0.05, indicating an influence on the decision to become a customer of a Sharia bank (muamalat bank KCP Purwakarta). The influence of variables X1, X2 and X3 simultaneously on Y is 19.0%. While the rest is the influence of other factors not examined by researchers.